KONSUMERISME GEN Z DAN TINGKAT GAGAL BAYAR: PENDEKATAN MAQASHID SYARIAH DALAM EKONOMI DIGITAL - Shofa Robbani; Dwi Anjani; Moch. Darul I; Mey Shofi Nurmawati; Aditya Jefri Ardiansyah (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
This study aims to analyze the relationship between Generation Z consumerism and default risk in the digital economy through the Maqashid Shariah approach. This research uses normative legal research with conceptual, statutory, and Maqashid Shariah approaches. Data were obtained through library research on the Qur’an, digital financial regulations, DSN-MUI fatwas, official reports, and relevant scholarly articles. The findings show that low financial literacy, easy access to paylater services, consumptive lifestyles, and weak self-control are the main factors increasing default risk. From the perspective of Maqashid Shariah, this phenomenon contradicts the principles of hifz al-mal and hifz al-aql because it can damage wealth management and weaken rationality in economic decision-making.